Teaching Materials Based on Socio Scientific Issues: An Effective Strategy to Improve Science Literacy and Critical Thinking Skills - Neli Wisdayana; Achyani; Arif Rahman Aththibby (Postgraduate, University of Mataram, 2025)
The low level of science literacy and critical thinking as well as the lack of contextual teaching materials encourage the development of more relevant and meaningful teaching materials. This study aims to analyze the effectiveness of Socio-Scientific Issues (SSI)-based teaching materials in improving students' science literacy and critical thinking skills. The study used a quasi-experimental method with a Pretest-Posttest Control Group design involving 120 students from SMPN 1 Bandar Negeri Semuong and SMPN 1 Wonosobo. Data were collected through pretests and posttests that measured science literacy and critical thinking skills, then analyzed using the Mann-Whitney test because the data were not normally distributed. The results showed that the experimental group using SSI-based teaching materials had a higher n-Gain score in both science literacy (0.71, high category) and critical thinking skills (0.71, high category) than the control group. The value of Asymp. Sig. (2-tailed) value of 0.000 indicates a significant difference between the two groups. This finding indicates that SSI-based teaching materials are effective in improving students' science literacy and critical thinking skills through the presentation of relevant socio-scientific issues that encourage analysis, evaluation, and inference. Thus, the application of SSI-based teaching materials can be an innovative strategy to improve the quality of science learning.